1976
DOI: 10.1038/bjc.1976.78
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole (Flagyl): characterization as a cytotoxic drug specific for hypoxic tumour cells

Abstract: Summary.-The cytocidal properties of metronidazole against hypoxic mammalian cells are described. This chemotherapeutic action has been shown to be dependent on drug concentration and duration of exposure. The x-ray TCD50 for a murine anaplastic carcinoma was reduced from 6081 rad to 4643 rad when animals were given metronidazole orally for 36 h before radiation treatment. The effect is attributed to the direct killing of hypoxic tumour cells by a mechanism analogous to that proposed for the action of the drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
1

Year Published

1977
1977
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…Fewer experiments have been performed with these intra-tumour measurements than the total number of experiments in this series. The data demonstrate that the toxic effect of Ro-07-0582 is marked at intra-tumour temperatures of more than 42*5°C, whereas at intra-tumour tempera- In vitro cytotoxicity to metronidazole (2-methyl-5-nitroimidazole-1-ethanol) has been reported by Sutherland (1974) and Mohindra and Rauth (1976) and, in vivo, by Inch and McCredie (1975) and Foster et al (1976). In vitro hypoxic cell cytotoxicity of Ro-07-0582 has been reported by Sutherland et al (1976) and Hall and Roizin-Towle (1975).…”
Section: Methodsmentioning
confidence: 63%
See 3 more Smart Citations
“…Fewer experiments have been performed with these intra-tumour measurements than the total number of experiments in this series. The data demonstrate that the toxic effect of Ro-07-0582 is marked at intra-tumour temperatures of more than 42*5°C, whereas at intra-tumour tempera- In vitro cytotoxicity to metronidazole (2-methyl-5-nitroimidazole-1-ethanol) has been reported by Sutherland (1974) and Mohindra and Rauth (1976) and, in vivo, by Inch and McCredie (1975) and Foster et al (1976). In vitro hypoxic cell cytotoxicity of Ro-07-0582 has been reported by Sutherland et al (1976) and Hall and Roizin-Towle (1975).…”
Section: Methodsmentioning
confidence: 63%
“…Small changes in temperature over the range 42-45°C may produce large changes in cell killing. It has also been reported that hypoxic cells are more sensitive to killing by heat than in oxic cells (Gerweck et at., 1974;Kim et at., 1975a). The surviving fractions assayed in this paper will therefore be a product of the temperature and hypoxic cell gradients.…”
Section: Figurementioning
confidence: 94%
See 2 more Smart Citations
“…Also, poorly nourished tumour cells tend to be slowly proliferating (Tannock, 1968(Tannock, , 1970Hirst & Denekamp, 1979) whereas most anti-cancer drugs are more active against rapidly proliferating cells (Tannock, 1978 Taylor & Rauth, 1978) and to induce necrosis of hypoxic cells in the centre of multicellular spheroids (Sridhar et al, 1976). At high concentration, the same drugs have good penetration into hypoxic regions of tumours, and have been shown to kill hypoxic cells in some, but not all, mouse tumours (Foster et al, 1976;Brown, 1977;Denenkamp, 1978;Pederson et al, 1979). Also MISO may be metabolized in hypoxic tumour regions, with release of metabolites that can kill neighbouring better-oxygenated cells (Brown, 1977;Brown & Yu, 1979).…”
mentioning
confidence: 99%